USING DUOCARDS APPLICATION IN IMPROVING STUDENTS’ VOCABULARY MASTERY - Yusuf, Andi Muallimah; Ariyani, Amra; Korompot, Chairil Anwar (Universitas Negeri Makassar, 2024)
Meaning, spelling, pronunciation, word classes, and word use are the five main focus areas of this study as it explores how students might use the Duocards application to increase their vocabulary mastery. Fourteen eighth-grade students from SMP Negeri SATAP Sering in Soppeng, South Sulawesi, selected by cluster random sampling, participated in this study using a pre-experimental design. To collect data, vocabulary tests were given as pretests and posttests. SPSS 26 was then used for analysis. The average pretest score increased from 37.71 to 73.78 in the posttest, indicating a considerable improvement in the students’ vocabulary competence, according to the data. Furthermore, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted because the two-tailed significance value was 0.000, less than 0.005. These findings suggest that the Duocards application has improved the students’ vocabulary mastery.